Exploring political orientation: a comparative analysis of news media and government responses to the Russia-Ukraine conflict - Seongkyu Ko; Junyeop Cha; Eunil Park; Angel P. del Pobil (Humanities & Social Sciences Communications)
Abstract On February 24, 2022, the Russian government launched a “special military operation," triggering the Ukraine-Russia conflict. In response, the United States government condemned Russia’s actions and continued to provide economic and military support to Ukraine. However, within U.S. society, policy perspectives on Ukraine varied depending on political orientation. To analyze these differences, we collected news articles produced by U.S. media outlets and examined the distinctions between conservative and progressive sources. For the analysis, we used a word-frequency-based psycholinguistic analysis tool to construct seven word categories. Subsequently, we developed a classification model based on the collected articles and applied it to categorize official government documents according to their political orientation. The model classified 291 documents, identifying 64 as conservative and 227 as progressive. Additionally, we employed topic modeling to measure the similarity between conservative and progressive media. Using Jensen-Shannon Divergence (JSD), we found that government documents exhibited a greater similarity to conservative media sources. Furthermore, we analyzed the implicit intentions embedded within official government documents. This study demonstrates the feasibility of using computational methods to measure political orientation in texts produced by news media and government sources regarding the Russia-Ukraine conflict.